Model Student Self Assessment for Geography Teacher at MAN - Darni, Darni; Akmal, Akmal; Ramadhan, Dewi; Ismail, Ismail (Postgraduate School, Universitas Negeri Padang, 2023)
Assessment model research student self-assessment aims to; 1) analyze and formulate Student Self assessment instruments Assessment which will be used by geography teachers at MAN Pekanbaru City; and 2) find a new product in the formula instrument student self-assessment assessment that meets the admission requirements namely: validity requirements, practicality, and effectiveness. This study used a qualitative descriptive method, a Research and Development (R&D) type of research. The research sample was geography teachers at MAN 1, MAN 2, MAN 3, and MAN 4 in Pekanbaru City. The results of the study revealed 1) the results of the field findings illustrated that the teachers in the schools that were the research sample did not yet have instrument student self-assessment conducted before learning begins. Based on the results of the evaluation and analysis of the results of product trials carried out in sample schools at MAN 1, MAN 2, MAN 3, and MAN 4, the average score for the assessment of instrument products was 2.75 (quite a good qualitative value); and 2) Instrument products evaluation student self-assessment, the results of the study stated that they had fulfilled three acceptance requirements, namely the requirements of validity, practicality, and effectiveness.